1999
DOI: 10.1177/107049659900800402
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Environmental Behavior in Manufacturing Plants in Indonesia

Abstract: This article reports on a survey of the environmental behaviors of manufacturing plants in a large industrial city in Indonesia. The survey identified plant-level environmental behaviors and measured the extent of exposure of plants to regulatory, community, and market pressures and to government incentives designed to get plants to install pollution control equipment. Statistical findings show that plant characteristics, regulatory actions, community and market pressures, and government incentives all influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Studies on environment issues in the Indonesia context are more concerned with the effectiveness of forest management certification programs to improve environmental, social, and economic performance over existing management practices (Miteva et al , 2015) and the effectiveness of environmental impact assessment regarding the protection of the marine environment from industrial pollution (Syafiq, 2015). Moreover, Rock and Aden (1999) investigated the influence of plant characteristics, regulatory actions, community and market pressures, and government incentives on plant investment in pollution control. In regard to environmental issues and firm performance, Rokhmawati et al (2015) found that CO2e intensity and social reporting scores have a positive and significant effect on firm performance (ROA).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on environment issues in the Indonesia context are more concerned with the effectiveness of forest management certification programs to improve environmental, social, and economic performance over existing management practices (Miteva et al , 2015) and the effectiveness of environmental impact assessment regarding the protection of the marine environment from industrial pollution (Syafiq, 2015). Moreover, Rock and Aden (1999) investigated the influence of plant characteristics, regulatory actions, community and market pressures, and government incentives on plant investment in pollution control. In regard to environmental issues and firm performance, Rokhmawati et al (2015) found that CO2e intensity and social reporting scores have a positive and significant effect on firm performance (ROA).…”
Section: Introductionmentioning
confidence: 99%
“…That monitoring and enforcement are important for the success of the Clean River Program not only follows from the record of West Java in this respect, as mentioned above, but was also emphasized by a study by Rock and Aden (1999) on the performance and outcomes of this program in Semarang. These authors noted a strong correlation between enforcement actions and investment in pollution abatement equipment.…”
Section: Decentralization's Impact On Water Pollution Control 24mentioning
confidence: 85%
“…However, gradually the program has changed to a more mandatory format and provided the provinces an increasingly serious role in monitoring and enforcement. It should be noted, though, that monitoring of effluent was much more difficult for the provincial authorities than for the Department of Industries, as the latter did have access to the factories, whereas the former could only monitor their performance by taking samples of river water (Rock and Aden 1999).…”
Section: Decentralization's Impact On Water Pollution Control24mentioning
confidence: 99%
“…In a survey of 92 textile and petrochemical plants in Korea, Rock & Aden (1999) looked at the determinants of plant-level pollution abatement expenditures. They found that employment, plant-level sales, foreign ownership, an index of government sanctions and community pressure all had significant and positive effects on abatement expenditures.…”
Section: Firm Characteristics and Environmental Management And Performentioning
confidence: 99%